Process optimization and eco-friendly/greener synthesis of some n-aryl/heteryl acetoacetamides (International Current Pharmaceutical Journal, 2013)
N-aryl/heteryl acetoacetamides are the intermediates used in the synthesis of various heterocyclic compounds like 1,4-dihydropyridines, pyrimidines etc. Three different substituted N-aryl/heteryl acetoacetamide derivatives (I-III) have been prepared from the reaction of ethylacetoacetate and three different aryl/heteryl primary amines under solvent free conditions using potassium tert-butoxide as catalyst. The reactions were carried out by two different methods (viz., Conventional and Microwave irradiation) and they are simple, eco-friendly and economical. All reactions were processed for optimization with different ratios of aryl/heteryl amine and ethylacetoacetate like1:1,1:1.2,1:1.4,1:1.6,1:1.8,1:2 and a comparison was made between the percentage yields with each ratio. Highest percentage yield was observed with 1:1.8 ratio for I & II and 1:1.6 ratio for III in both the methods. However, the microwave irradiation method was found to be superior to the conventional method. The newly synthesized compounds have been purified by recrystallization and characterized by physical and spectral data.DOI: http://dx.doi.org/10.3329/icpj.v2i11.16533 International Current Pharmaceutical Journal, October 2013, 2(11): 189-192